IDENTITAS PETANI YANG MEMPENGARUHI PENDAPATAN BAGI USAHATANI PADI SAWAH DI KOTA BAUBAU - Hardin Hardin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2019)
The internal variables that can increase productivity and income, including schooling, age, arable land size and the number of dependents and the experience of agriculture and social status are all linked to the identity of farmers. The aim of this study is: (1) Empirically demonstrate that the age of farmers is influenced by rice farming income in the village of Ngkaringkaring, subdistrict of Bungi and city of Baubau; (2) empirically demonstrate that there is an impact on rice crop income in Ngkaringkaring Village and Bungi Subdistrict and Baubau City on farmers ' education; (3) Demonstrate empirically whether the number of dependents of the farming family has an impact on the income of lowland rice farming in Ngkaringkaring Village, subdistrict of Bungi, the city of Baubau; (4) Demonstrate empirically whether farmers ' experience has an impact on the income of lowland rice farming in Ngkaringkaring Village, subdistrict of Bungi, Baubau City; (5) (5) To prove empirically whether farmers have an impact on the income of lowland rice farmers in Ngkaringkaring Village, subdistrict of Bungi, Baubau City; (6) To prove empirically whether the social status of farmers has an impact on the income of rice farming in Ngkaringkaring Village, subdistrict of Bungi, Baubau City. The technique used is a multi-linear regression method. The results of this study are: (1) The level of education and area of arable land and the effect of income on lowland rice farming with a probability value of 0.000 each well below 0.05 means that H0 is rejected and H2 and H5 accepted; (2) Age, farming experience, number of family dependents and social status do not affect rice farming income, as each has a probably. (3) The identity of the respondent farmers (age, level of education, farming experience, number of family dependents, area of arable land and social status) together contributed 96.4 percent to the income effect on lowland rice farming, while the remaining 3.6 percent were affected by other factors. Keywords: Farmer Identity, Rice Field Farming Income